201 OVERESTIMATION OF GLOMERULAR FILTRATION RATE USING THE MODIFICATION OF DIET IN RENAL DISEASE EQUATION IN CHRONIC SPINAL CORD INJURY. (1st January 2005) - Grant, N. D.; Zaidi, S. J.A.; Mangold, T. M.; Wall, B. M.
Abstract : The purpose of the current study was to determine the accuracy of the simplified modification of diet in renal disease (MDRD) equation in predicting GFR, as compared to 24-hr urine collections for creatinine clearance (Ccr) obtained from 116 chronic spinal cord injury (SCI) patients with Ccr < 90 mL/min/1.73m2. Urine collections were considered adequate if there was > 10 mg/kg of creatinine in quadriplegic and > 15 mg/kg in paraplegic subjects. GFR was calculated using the simplified MDRD equation utilizing age, gender, ethnicity, and serum creatinine. Linear regression analysis was performed relating predicted GFR to measured Ccr. There was a highly significant correlation between measured Ccr and predicted GFR; however, the relationship was much more variable in quadriplegic subjects: All SCI subjects (n = 116), r = .61, r2 = 0.38, p < .001. Paraplegics (n = 64), r = .75, r2 = .56, p < .001. Quadriplegic (n = 52), r = .42, r2 = .17, p < .01. Figures below are shown with line of unity between Ccr and predicted GFR.